2008
DOI: 10.1055/s-0028-1087392
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Cyclization of Sulfamate Esters Using NaOCl - A Metal-Mediated Hoffman-Löffler-Freytag Reaction

Abstract: Intramolecular C-H amination with sulfamate esters occurs under the action of dinuclear Rh catalysts and iodine(III) oxidants, and has recently emerged as a powerful tool for synthesis. Insights gained through mechanistic studies of this process suggest that other terminal oxidants, including common halogenating agents such as NaOCl, could function to promote the cyclization reaction. Results described in this report demonstrate that the combination of NaOCl and 3 mol% Rh 2 (oct) 4 is effective in select cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…These data further support a stepwise mechanism for manganese that proceeds through H–atom abstraction followed by rapid radical rebound from the base metal catalyst. In contrast to aminations that proceed via free radical intermediates 21,38,39 , this mechanistic feature of metallonitrene chemistry allows C—H amination reactions to proceed stereospecifically with high functional group tolerance, and enables the prospect of tuning the catalyst to control selectivity during functionalization 6 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These data further support a stepwise mechanism for manganese that proceeds through H–atom abstraction followed by rapid radical rebound from the base metal catalyst. In contrast to aminations that proceed via free radical intermediates 21,38,39 , this mechanistic feature of metallonitrene chemistry allows C—H amination reactions to proceed stereospecifically with high functional group tolerance, and enables the prospect of tuning the catalyst to control selectivity during functionalization 6 .…”
Section: Resultsmentioning
confidence: 99%
“…We hypothesized that a metal catalyst capable of transferring bound nitrenes to C(sp 3 )—H bonds via a stepwise mechanism with attenuated radical character of the metallonitrene oxidant relative to iron would achieve higher reactivity while maintaining chemoselectivity 20 . Low reactivity observed under iron catalysis with aliphatic C(sp 3 )—H bonds coupled with reports that sulfamate ester N -centered free radicals are unreactive towards intramolecular aminations of 3° C(sp 3 )—H bonds 21 suggested to us that a metallonitrene with diminished radical character would be more reactive. Although nature rarely uses manganese metal species to mediate oxidations, early studies using synthetic metalloporphryins as models for cytochrome P450 demonstrated that manganese and iron oxos react via mechanistically analogous one electron pathways, with manganese exhibiting significantly higher C—H hydroxylation reactivity 22 .…”
mentioning
confidence: 80%
“…To our knowledge, there are no general strategies for aliphatic γ-C–H functionalization guided by a masked alcohol. [4,5] Herein described are the first experiments to demonstrate that sulfamate esters [6,7] can mediate 1,6-hydrogen-atom transfer (HAT) processes to guide the light-promoted chlorination of unactivatedγ-C(sp 3 )–H centers.…”
mentioning
confidence: 99%
“…In unguided C–H functionalization reactions, proximity to inductively electron-withdrawing groups deactivates C–H bonds to oxidation. This phenomenon is evident when 3,7-dimethyloctanol is masked with an electron withdrawing group, and engages in undirected fluorination, [33] oxygenation, [34] amination, [35] azidation, [36] or trifluoromethylthiolation [37] processes that functionalize C(7) in preference to C(3). By contrast, the sulfamate ester-guided chlorination installs chlorine at the electronically deactivated C(3) position (entries 2–3).…”
mentioning
confidence: 99%
“…A variety of transition metal salts were tested in conjunction with 3 equivalents each of NaBr and NaOCl, a reagent combination known to generate hypobromite in situ and used previously for the oxidative cyclization of sulfamate esters. 56 While little to no reaction ensued in the presence of catalytic Mn 3+ , Co 2+ , Cu 2+ , and Ni 2+ ( Table 1 , entries 1–4), switching to Rh 2 (oct) 4 ( Table 1 , entry 5) afforded a marked increase in conversion to brominated product 2 . The choice of dirhodium complex had a clear influence on reaction performance, as catalysts bearing hydrophobic ligands such as octanoate or triphenylacetate ( Table 1 , entries 5–7) out-performed others tested ( Table 1 , entries 8, 9), likely owing to the greater solubility of these complexes in dichloromethane.…”
Section: Resultsmentioning
confidence: 99%